Impact of the COVID-19 pandemic on the prevalence of respiratory viral pathogens in patients with acute respiratory infection in Shanghai, China - Pan, Lifeng; Yuan, Yang; Cui, Qiqi; Zhang, Xuechun; Huo, Yujia; Liu, Qing; Zou, Wenwei; Zhao, Bing; Hao, Lipeng (Frontiers in Public Health, 2024)
Objective This study aimed to evaluate the impact of nonpharmaceutical interventions (NPIs) taken to combat COVID-19 on the prevalence of respiratory viruses (RVs) of acute respiratory infections (ARIs) in Shanghai. Methods Samples from ARI patients were collected and screened for 17 respiratory viral pathogens using TagMan low density microfluidic chip technology in Shanghai from January 2019 to December 2020. Pathogen data were analyzed to assess changes in acute respiratory infections between 2019 and 2020. Results A total of 2,744 patients were enrolled, including 1,710 and 1,034 in 2019 and 2020, respectively. The total detection rate of RVs decreased by 149.74% in 2020. However, detection rates for human respiratory syncytial virus B (RSVB), human coronavirus 229E (HCoV229E), human coronavirus NL63 (HCoVNL63), and human parainfluenza virus 3 (HPIV3) increased by 91.89%, 58.33%, 44.68% and 24.29%, in 2020. The increased positive rates of RSVB, HPIV3, resulted in more outpatients in 2020 than in 2019. IFV detection rates declined dramatically across gender, age groups, and seasons in 2020. Conclusion NPIs taken to eliminate COVID-19 had an impact on the prevalence of respiratory viral pathogens, especially the IFVs in the early phases of the pandemic. Partial respiratory viruses resurged with the lifting of NPIs, leading to an increase in ARIs infection.